2022
DOI: 10.5334/pb.1088
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Relationships in Times of COVID-19: A Descriptive Study of Belgian Partners and their Perceived Well-Being

Abstract: How did couples in Belgium cope during the early phases of the COVID-19 pandemic? In this study, grounded in relationship science, we investigated in a descriptive manner several factors that could affect how couples perceived individual and relational wellbeing during this time. Specifically, we examined the associations between gender, sexual orientation, parental status, and relationship duration on participants' selfreported individual and relational well-being after the first lockdown (more generally and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(85 reference statements)
0
3
1
Order By: Relevance
“…Finally, the impact of the pandemic on we-ness did not vary as a function of the presence of children at home, participants’ gender, or the duration of their relationship, which was consistent with our previous study (Galdiolo et al, 2022b). The finding that there were no differences in our variables of interest between couples with or without children at home is, however, inconsistent with previous research (e.g., Sels et al, 2022) showing that partners without children reported higher levels of relationship quality than parents during the lockdown. One explanation for this inconsistency is that participants’ reports about interactions during the lockdown often referred to couple as well as to family interactions.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, the impact of the pandemic on we-ness did not vary as a function of the presence of children at home, participants’ gender, or the duration of their relationship, which was consistent with our previous study (Galdiolo et al, 2022b). The finding that there were no differences in our variables of interest between couples with or without children at home is, however, inconsistent with previous research (e.g., Sels et al, 2022) showing that partners without children reported higher levels of relationship quality than parents during the lockdown. One explanation for this inconsistency is that participants’ reports about interactions during the lockdown often referred to couple as well as to family interactions.…”
Section: Discussioncontrasting
confidence: 99%
“…While much of daily life around the world adapted to major changes, the risk of prolonged and severe impacts on mental health were widely identified, with large increases in depression, anxiety, stress, and other common mental disorders reported globally 127 . In some cases, these effects were moderated (or at least attenuated) by being isolated along with close others 128 , while other studies showed dramatic increases in intimate partner violence and violence against women 129,130 . Though not able to circumvent all aspects, in line with the 2020 article, some positive mental health outcomes had direct links to mindset and perspective 131 .…”
Section: Stress and Copingmentioning
confidence: 97%
“…And this impacted their mental health, therefore creating distress, and work conditions, especially when there were children in the household (Chauhan, 2021;Leonard et al, 2022;Power, 2020;Yildirim & Eslen-Ziya, 2021). Despite other authors reporting that children in the household was a protection factor for well-being and coping during the Coronavirus lockdown (Mari et al, 2020;Sels et al, 2022) In the Dominican Republic this was evidenced in a report about use of time during Covid-19 by Morales Pacheco & Tatem Brache (2020). They found that women saw an increment in their reproductive and unpaid work where they had to take care of children's education, plus the caregiving, healthcare, and emotional support of the family.…”
Section: Discussionmentioning
confidence: 99%